Methodical features of the teaching of mathematics for the future primary school teachers (Pedagogy of Higher and Secondary Education, 2014)
Tarasenkova N. A., Kovalenko O. A. Methodical features of the teaching of mathematics for the future primary school teachers.The article deals with one of the didactic approaches of systematizing the knowledge of theoretical material on «Expressions» of students and improving their skills to solve practical and creative tasks that makes awareness of the future primary school teacher in the content of the educational material in mathematics and contributes to the formation of his professional competence.
Keywords: future primary school teachers; teaching mathematics; expressions; expressions with variables; competence; training